Beta2‐adrenoceptor agonist salbutamol increases protein turnover rates and alters signalling in skeletal muscle after resistance exercise in young men. (30th July 2018) - Hostrup, Morten; Reitelseder, Søren; Jessen, Søren; Kalsen, Anders; Nyberg, Michael; Egelund, Jon; Kreiberg, Michael; Kristensen, Caroline Maag; Thomassen, Martin; Pilegaard, Henriette; Backer, Vibeke; Jacobson, Glenn A.; et al.
Abstract : Key points: Animal models have shown that beta2 ‐adrenoceptor stimulation increases protein synthesis and attenuates breakdown processes in skeletal muscle. Thus, the beta2 ‐adrenoceptor is a potential target in the treatment of disuse‐, disease‐ and age‐related muscle atrophy. In the present study, we show that a few days of oral treatment with the commonly prescribed beta2 ‐adrenoceptor agonist, salbutamol, increased skeletal muscle protein synthesis and breakdown during the first 5 h after resistance exercise in young men. Salbutamol also counteracted a negative net protein balance in skeletal muscle after resistance exercise. Changes in protein turnover rates induced by salbutamol were associated with protein kinase A‐signalling, activation of Akt2 and modulation of mRNA levels of growth‐regulating proteins in skeletal muscle. These findings indicate that protein turnover rates can be augmented by beta2 ‐adrenoceptor agonist treatment during recovery from resistance exercise in humans. Abstract: The effect of beta2 ‐adrenoceptor stimulation on skeletal muscle protein turnover and intracellular signalling is insufficiently explored in humans, particularly in association with exercise. In a randomized, placebo‐controlled, cross‐over study investigating 12 trained men, the effects of beta2 ‐agonist (6 × 4 mg oral salbutamol) on protein turnover rates, intracellular signalling and mRNA response in skeletal muscle were investigated 0.5–5 h after quadriceps resistance exercise. Each trial was preceded by a 4‐day lead‐in treatment period. Leg protein turnover rates were assessed by infusion of [ 13 C6 ]‐phenylalanine and sampling of arterial and venous blood, as well as vastus lateralis muscle biopsies 0.5 and 5 h after exercise. Furthermore, myofibrillar fractional synthesis rate, intracellular signalling and mRNA response were measured in muscle biopsies. The mean (95% confidence interval) myofibrillar fractional synthesis rate was higher for salbutamol than placebo [0.079 (95% CI, 0.064 to 0.093) vs . 0.066 (95% CI, 0.056 to 0.075%) × h −1 ] ( P < 0.05). Mean net leg phenylalanine balance 0.5–5 h after exercise was higher for salbutamol than placebo [3.6 (95% CI, 1.0 to 6.2 nmol) × min −1 × 100 gLeg Lean Mass −1 ] ( P < 0.01). Phosphorylation of Akt2, cAMP response element binding protein and PKA substrate 0.5 and 5 h after exercise, as well as phosphorylation of eEF2 5 h after exercise, was higher ( P < 0.05) for salbutamol than placebo. Calpain‐1, Forkhead box protein O1, myostatin and Smad3 mRNA content was higher ( P < 0.01) for salbutamol than placebo 0.5 h after exercise, as well as Forkhead box protein O1 and myostatin mRNA content 5 h after exercise, whereas ActivinRIIB mRNA content was lower ( P < 0.01) for salbutamol 5 h after exercise. These observations suggest that beta2 ‐agonist increases protein turnover rates in skeletal muscle after resistance exercise in humans, with concomitant cAMP/PKA and Akt2 signalling, as well as modulation of mRNA response of growth‐regulating proteins. Key points: Animal models have shown that beta2 ‐adrenoceptor stimulation increases protein synthesis and attenuates breakdown processes in skeletal muscle. Thus, the beta2 ‐adrenoceptor is a potential target in the treatment of disuse‐, disease‐ and age‐related muscle atrophy. In the present study, we show that a few days of oral treatment with the commonly prescribed beta2 ‐adrenoceptor agonist, salbutamol, increased skeletal muscle protein synthesis and breakdown during the first 5 h after resistance exercise in young men. Salbutamol also counteracted a negative net protein balance in skeletal muscle after resistance exercise. Changes in protein turnover rates induced by salbutamol were associated with protein kinase A‐signalling, activation of Akt2 and modulation of mRNA levels of growth‐regulating proteins in skeletal muscle. These findings indicate that protein turnover rates can be augmented by beta2 ‐adrenoceptor agonist treatment during recovery from resistance exercise in humans.